2019
DOI: 10.3389/fmars.2019.00587
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Harmful Algae Bloom Monitoring via a Sustainable, Sail-Powered Mobile Platform

Abstract: Weight 85 lbs plus payload Rigging Main + Jib "storm" sails and chafe resistant lines Mast Unstayed reinforced carbon Winch Electric with anti-jamming spool Rudder and Keel No-tangle design sheds lines and seaweed Power 12 V, 35 W solar array Batteries Up to 120 Ah LiFePO 4 Standard sensors GPS, PRH, Meteorological, AIS (passive receiver on ASV for informing the operator of the location of nearby ships via the iPad application) Optional sensors Water quality: O 2 , CT, backscatter, 3/6 channel fluorometer (chl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Recently the field is advancing in the direction of deploying in situ sensors on longer-term platforms monitored by satellites (or ship cruises) (Whitt et al, 2020). Examples of imaging instruments include moored (Seegers et al, 2015;Yamahara et al, 2015;Ryan et al, 2017;Bowers et al, 2018), ship-based (Schofield et al, 2006), remotely operated underwater vehicles (ROVs) and autonomous underwater vehicles (AUVs) (Hails et al, 2009;Pargett et al, 2015;Beckler et al, 2019). These applications significantly advance the spatiotemporal coverage compared to earlier efforts with ship-based sampling.…”
Section: In Situ Sensors For Imaging and Omics In Unmanned Autonomous...mentioning
confidence: 99%
“…Recently the field is advancing in the direction of deploying in situ sensors on longer-term platforms monitored by satellites (or ship cruises) (Whitt et al, 2020). Examples of imaging instruments include moored (Seegers et al, 2015;Yamahara et al, 2015;Ryan et al, 2017;Bowers et al, 2018), ship-based (Schofield et al, 2006), remotely operated underwater vehicles (ROVs) and autonomous underwater vehicles (AUVs) (Hails et al, 2009;Pargett et al, 2015;Beckler et al, 2019). These applications significantly advance the spatiotemporal coverage compared to earlier efforts with ship-based sampling.…”
Section: In Situ Sensors For Imaging and Omics In Unmanned Autonomous...mentioning
confidence: 99%
“…The Turner Cyclops fluorometers used here have been used in many other studies for monitoring algal blooms in marine and freshwater. ,− They have also been tested in trials by the Alliance for Coastal Technologies and showed comparable results to other commercially available fluorometers . Although they have limitations, at least one study shows that they are useful for monitoring large increases in pigments, indicative of bloom conditions .…”
Section: Discussionmentioning
confidence: 99%
“…In the use of multiparametric probes, Zamydi et al [150] detected cyanobacteria (Phycocyanin and Chlorophylla) in the Yamaska River Reservoir and Lake Champlain Bay, Canada, using the fluorescence technique and the YSI 6600 V2-4 probe. Beckler et al [151] were also able to monitor and map the algae bloom on the coast in an automated way using a fluorometer sensor (Cyclops Integrator/C3) coupled to a remotely operated boat (Navocean Nav2 ASV). Naughton et al [152] monitored microalgae on an aquaculture farm for 10 months using the AlgaeTorch Âź probe, in the Republic of Ireland, as a tool for monitoring seasonal changes in cultivation and for decision-making by producers.…”
Section: Yamahara Et Al [153] Polymerase Chain Reactionmentioning
confidence: 99%